Principles of marketing - Kotler, Philip; Armstrong, Gary (Gary M.); Balasubramanian, Sridhar (2024)
"The nineteenth edition of Principles of Marketing reflects the major trends and shifting forces that impact marketing in this digital age of customer value, engagement, and relationships"--
Revised edition of Principles of marketing, 2019.
Includes bibliographical references and index.
Keywords: Marketing